A Conceptual View of Poisonous and Non-Poisonous Leeches in Ayurveda - DEVENDRA P MISHRA (Dr. Chinmay Pandya, 2015)
Leeches are being used by of human kind for centuries for treating many disorders. Though it is very useful tool and is propagating throughout the world as a special medical device, side effects of leech bites in some cases have been found from time to time. It is because of improper knowledge of non-poisonous and poisonous leeches. Sushruta's classification shows us the passage to the proper use of leeches for leech therapy. In this study, Sushruta's classification of leeches was compared and paired with that of phylum Annelida and was found effective in scientifically differentiating between non-poisonous and poisonous leeches.